The Effect of Sitrate Acid addition towards Organoleptic Properties of Jackfruit jam - Mustamir Anwar Masuku (Sangia Publishing, 2021)
The research aims to determine the organoleptic jeck fruit jam in creased with addition of citric acid. With the added treatmen the are P0 = without the eddition of preservatives (control), P1 = citric acid 1g, P2 = ctric acid 2g, P3 = citric acid 3g. Organoleptic test are carried out based on the method of this research is in the form of a unit experiments. Then analysis that include organoleptic properties such as : color,aroma, an texture. Treatmen of all the differen eddition of citric acid didnet no significant of effect on the parametersare color and aroma. While the texture of real effect on the organoleptic propertiest of jack fruit jam whit citric acid added to the color 4,35-4,43 (brownish, very brownish) aroma 3,90-4,2 ( veri flaforful jack fruit) 3,98-4,28 (soft very –soft). The bets jack fruit jam in this study is determined by giving rank, rank the smallest is the bets. Of all the best jack fruit jam treatmentin this study is the jack fruit jam with the addition of citric acid 2 g (p2) with the results organoleptic the color is 4.48, aroma 4.24, and texture 4.33.